Implikasi Pengadaan Barang dan Jasa secara Elektronik bagi Efisiensi Keuangan dan Optimalisasi Fungsi Pemerintahan - Maulana Mukhlis; Rahmat Pranoto (ARISTO, 2020)
One of bureaucracy reformation demands in Indonesia is improvement in procurement of goods/service for government as results of many corruption, collusion, and nepotism cases, and inefficiency in the process of that procurement. Reformation in the procurement is then realized in the electronic procurement (e-procurement) implementation. In the government perspective, e-procurement is conducted as an effort to prevent corruption, collusion, and nepotism. In the context of service acceleration, e-procurement is the manifestation of new public management paradigm; an effort to improve service quality by encouraging entrepreneurship spirit to realize efficiency of state finance use without reducing qualities of /services that are required by government institutions. This research was conducted with qualitative method with an objective to explore the implication of e-procurement for the efficiency of state finance use and improvement of service function in Lampung University. The result showed that there were three aspects of efficiency: time efficiency, cost efficiency, and efficiency of all outcomes had been attained. In the perspective of time, the common auction process if it was conducted manually it would require minimum time of 28 working days, and it would take only 20 working days by e-procurement method. In the cost perspective, the fund demand for transportation cost (registration and submitting offering), communication cost (joining meeting for explanation), duplication cost (duplicating auction documents), and printing cost (offering documents) could be eliminated by replacing them by on-line method. The e-procurement enactment quantitatively in Lampung University in 2013-2014 produced financial efficiency by 22.4% and this indicated efficiency of outcomes. As results of this efficiency derivation, by having status of Common Service Agency (BLU) status, Lampung University possessed discretion to manage this 22.4% fund efficiency for optimizing funding activities for “three pillars of higher education” (tridharma perguruan tinggi) at the same year without waiting budget planning at the next fiscal year. Based on these findings, the e-procurement implementation in Lampung University had positive implication to obtain financial efficiency goal so that it would be a supporting factor for government function optimization, especially for “three pillars of higher education”.